Infection of central nervous system cells by ecotropic murine leukemia virus in C58 and AKR mice and in in utero-infected CE/J mice predisposes mice to paralytic infection by lactate dehydrogenase-elevating virus. - Anderson, G W (1995)
Certain mouse strains, such as AKR and C58, which possess N-tropic, ecotropic murine leukemia virus (MuLV) proviruses and are homozygous at the Fv-1n locus are specifically susceptible to paralytic infection (age-dependent poliomyelitis [ADPM]) by lactate dehydrogenase-elevating virus (LDV). Our results provide an explanation for this genetic linkage and directly prove that ecotropic MuLV infection of spinal cord cells is responsible for rendering anterior horn neurons susceptible to cytocidal LDV infection, which is the cause of the paralytic disease. Northern (RNA) blot hybridization of total tissue RNA and in situ hybridization of tissue sections demonstrated that only mice harboring central nervous system (CNS) cells that expressed ecotropic MuLV were susceptible to ADPM. Our evidence indicates that the ecotropic MuLV RNA is transcribed in CNS cells from ecotropic MuLV proviruses that have been acquired by infection with exogenous ecotropic MuLV, probably during embryogenesis, the time when germ line proviruses in AKR and C58 mice first become activated. In young mice, MuLV RNA-containing cells were found exclusively in white-matter tracts and therefore were glial cells. An increase in the ADPM susceptibility of the mice with advancing age correlated with the presence of an increased number of ecotropic MuLV RNA-containing cells in the spinal cords which, in turn, correlated with an increase in the number of unmethylated proviruses in the DNA extracted from spinal cords. Studies with AKXD recombinant inbred strains showed that possession of a single replication-competent ecotropic MuLV provirus (emv-11) by Fv-1n/n mice was sufficient to result in ecotropic MuLV infection of CNS cells and ADPM susceptibility. In contrast, no ecotropic MuLV RNA-positive cells were present in the CNSs of mice carrying defective ecotropic MuLV proviruses (emv-3 or emv-13) or in which ecotropic MuLV replication was blocked by the Fv-1n/b or Fv-1b/b phenotype. Such mice were resistant to paralytic LDV infection. In utero infection of CE/J mice, which are devoid of any endogenous ecotropic MuLVs, with the infectious clone of emv-11 (AKR-623) resulted in the infection of CNS cells, and the mice became ADPM susceptible, whereas littermates that had not become infected with ecotropic MuLV remained ADPM resistant.